Correlación cirugía abdominal de urgencia vs emergencias quirúrgicas en pacientes con Covid19. Hospital Provincial General Docente. Riobamba, 2020-2021 - Parra Sánchez, Daniel Alejandro (2023)
ABSTRACT: The purpose of this research is to determine the correlation between urgent abdominal surgery and surgical emergencies in patients with Covid19 at the General Teaching Provincial Hospital of Riobamba, The COVID-19 pandemic has had a significant impact on healthcare and the performance of surgical procedures worldwide. Urgent abdominal surgery and surgical emergencies are procedures that can be affected by the presence of COVID-19 in patients. This thesis analyzes the correlation between urgent abdominal surgery and surgical emergencies in COVID-19 patients. Data are collected from COVID-19 patients who have undergone urgent or emergency abdominal surgery. The results of these surgeries are analyzed in terms of complications, mortality, and recovery time. It is also investigated whether the presence of COVID-19 in patients who need urgent or emergency abdominal surgery affects the decision of physicians to perform these procedures, and whether there is any difference in how COVID-19 patients are managed during and after surgery compared to patients who do not have COVID-19. The results indicate that the presence of COVID-19 in patients undergoing emergency or urgent abdominal surgery is not associated or related to a higher rate of complications and mortality. Additionally, physicians may be more hesitant to perform these procedures in COVID-19 patients due to concern for virus spread. Therefore, specific strategies are needed for the management of COVID-19 patients who require urgent or emergency abdominal surgery.